A synergistically modified asphalt and a method for preparing the same

CN122878772APending Publication Date: 2026-10-09SHAANXI TRANSPORTATION VOCATIONAL & TECH COLLEGE
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611384583.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-08
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

然而,在同时采用胶粉、SBS类弹性体和纳米二氧化硅时,各固相仍可能保持相对独立的迁移单元;增加无机粒子或提高交联程度虽可提高软化点,却可能形成较强的粒子网络并推高施工黏度

Benefits of technology

(1)马来酸酐接枝SBS先浸润预氧化胶粉,在体系接近浊点而尚未出现游离絮状物时引入氨基接枝纳米二氧化硅,使接枝纳米二氧化硅在包覆聚合物析出过程中共同进入胶粉外层。纳米二氧化硅表面的伯胺基可参与酸酐基开环反应,有利于减少纳米二氧化硅作为独立高密度颗粒迁移的倾向。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a kind of synergistically modified asphalt and preparation method thereof.Pre-oxidized rubber powder is prepared by hydrogen peroxide, and amino-grafted nano-silica is prepared by 3-aminopropyl triethoxysilane;Low water toluene solution of SBS grafted with maleic anhydride is used to infiltrate pre-oxidized rubber powder and calibrate V cloud point, then amino-grafted nano-silica is introduced after adding 0.70-0.85 V cloud point ethanol, and the molar ratio of total primary amine group to anhydride group is adjusted to 0.65-0.75 by flexible polyether diamine, wherein the primary amine group provided by grafted nano-silica accounts for 15%-35%;Continue to add ethanol to 1.5-2.5 V cloud point, and then obtain composite particles through aging, filtration, washing and drying;The modified asphalt is obtained by adding the composite particles to the base asphalt, shearing and developing.The method makes grafted nano-silica participate in the formation of rubber powder coating layer, which can reduce delamination and performance drift during high-temperature storage, and also considers construction viscosity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of polymer-modified asphalt technology for road engineering, and specifically to a synergistically modified asphalt and its preparation method. Background Technology

[0002] Waste tire rubber powder is a commonly used material for modifying asphalt with elastomers. It can improve the elasticity and temperature adaptability of asphalt and realize the resource utilization of waste tires. The rubber powder retains its vulcanized cross-linked structure, which differs from the density, polarity, and thermal motion state of asphalt. Therefore, it is prone to continued swelling, agglomeration, and migration during high-temperature storage. Even when nano-silica is added alone, it may settle or form a particle network due to density differences, high surface energy, and interactions between silanol groups. Simply increasing the viscosity of the system to suppress stratification would increase the resistance to conveying, pumping, and mixing.

[0003] CN103205131A discloses the preparation of modified rubber powder using ethanol, water glass, and rubber powder, so that silicate ions form a silica gel layer on the surface of the rubber powder; CN107936590B discloses the preparation of modified asphalt by coating waste tire rubber powder with amide polymers; CN110256745A discloses the mixing, cooling, and granulation of waste tire rubber powder, petroleum asphalt, SBS, and polyphosphoric acid; CN115678299B discloses the preparation of modified asphalt by oxidizing rubber powder with hydrogen peroxide and then treating it with fluorinated silane.

[0004] The aforementioned technologies improve the compatibility and storage stability of rubber-modified asphalt through methods such as rubber powder surface activation, inorganic layer deposition, polymer coating, or prefabrication of composite particles. However, when rubber powder, SBS-like elastomers, and nano-silica are used simultaneously, each solid phase may still maintain relatively independent migration units. While increasing inorganic particles or improving the degree of crosslinking can raise the softening point, it may also form a strong particle network and increase the working viscosity. Therefore, existing technologies struggle to maintain working fluidity while simultaneously ensuring the high-temperature storage stability of both rubber powder and nanoparticles, and suppressing compositional differences and performance drift during storage. Summary of the Invention

[0005] The purpose of this invention is to provide a synergistic modified asphalt and its preparation method, so as to reduce the relative migration and continued agglomeration of rubber powder and nano-inorganic particles during high-temperature storage and transportation, suppress compositional differences and performance drift during storage, and avoid increasing pumping and mixing resistance by simply increasing the viscosity of the system.

[0006] To achieve the above objectives, the present invention provides a method for preparing synergistically modified asphalt, comprising the following steps: (1) Waste tire vulcanized rubber powder was oxidized in aqueous phase with hydrogen peroxide solution. After oxidation, the residual peroxide was consumed with sodium bisulfite. The powder was then filtered, washed and dried to obtain pre-oxidized rubber powder.

[0007] (2) The hydrophilic nano silica was dispersed in an ethanol-water medium. 3-aminopropyltriethoxysilane was pre-hydrolyzed in an acidic ethanol-water medium and then added to the nano silica dispersion so that 3-aminopropyltriethoxysilane condensed with the surface of the nano silica. The nano silica was then separated, washed and dried to obtain amino-grafted nano silica.

[0008] (3) Dissolve maleic anhydride-grafted styrene-butadiene-styrene block copolymer in low-water toluene, add pre-oxidized rubber powder and stir to impregnate; prepare a standard sample with the same composition as the obtained master batch dispersion, add ethanol dropwise to the standard sample under the same temperature and stirring conditions as the master batch, and convert the ethanol volume when the turbidity lasts for 60s into the turbidity point ethanol volume V turbidity point of the master batch dispersion according to the mass ratio of the standard sample to the master batch dispersion; first add ethanol with a turbidity point of 0.70 to 0.85V to the master batch dispersion to make the system slightly opalescent and without visible free flocculent matter, then add the low-water toluene dispersion of amino-grafted nano silica, and simultaneously add ethanol during the addition process to maintain the aforementioned state; after the addition is completed, add flexible polyether diamine with a primary amine functionality of 2, and continue to add ethanol until the cumulative amount of ethanol added reaches 1.5 to 2.5V turbidity point, stir, let stand for ripening, filter, wash with ethanol and dry to obtain composite particles. Of which, based on 100 parts by weight of pre-oxidized adhesive powder (dry basis), maleic anhydride-grafted styrene-butadiene-styrene block copolymer is 20-25 parts by weight; the ratio of the total molar amount of primary amine groups of amino-grafted nano silica to the total molar amount of primary amine groups of flexible polyether diamine and the molar amount of anhydride groups of the block copolymer is 0.65-0.75, and the primary amine groups provided by amino-grafted nano silica account for 15%-35% of the total molar amount of primary amine groups.

[0009] (4) The composite particles are added to the base asphalt and then stirred, sheared and developed to obtain synergistically modified asphalt. The amount of the composite particles added is 15 to 20 parts by weight of the pre-oxidized rubber powder added during the preparation of the composite particles, based on 100 parts by weight of base asphalt.

[0010] In step (1), the cloud point V is calculated using the following formula: V cloud point = V sample × m master batch / m sample, where V sample is the volume of ethanol when the calibration sample reaches the endpoint, m master batch is the mass of the master batch of adhesive powder-polymer dispersion, and m sample is the mass of the calibration sample. The calibration sample uses the same specification container and the same liquid volume, and ethanol is added under the same temperature, stirring conditions, and constant dropping rate as the master batch. After stopping the dropping, if the system remains uniformly turbid for 60 seconds and there are no visible free flocculent substances, the cumulative volume of ethanol at that point is taken as V sample.

[0011] In step (1), the waste tire vulcanized rubber powder is 40-80 mesh, and the initial moisture content is not higher than 0.5%; the mass ratio of waste tire vulcanized rubber powder to hydrogen peroxide aqueous solution is 1:4-1:5, and the mass fraction of hydrogen peroxide aqueous solution is 20%-25%; the oxidation temperature is 60-70℃, and the oxidation time is 2-2.5h; after the oxidation is completed, the temperature is lowered to below 35℃, and a sodium bisulfite aqueous solution with a mass fraction of 5%-10% is added until the residual peroxide test is negative.

[0012] In step (2), the nominal primary particle size of the hydrophilic nano-silica is 10–30 nm, and the specific surface area is 150–250 m². 2 / g; based on 100 parts by mass of nano-silica, 3-aminopropyltriethoxysilane is 8-12 parts by mass; the mass ratio of ethanol to water in the pre-hydrolysis medium is 90:10-95:5, the pH is 4.5-5.5, the pre-hydrolysis temperature is 20-30℃, and the pre-hydrolysis time is 20-40 min; the condensation reaction temperature is 50-65℃, and the reaction time is 4-8 h; the available primary amine content of the obtained amino-grafted nano-silica is 0.25-0.45 mmol / g.

[0013] In step (3), the anhydride content of the maleic anhydride-grafted styrene-butadiene-styrene block copolymer is 0.12 to 0.22 mmol / g; the number average molecular weight of the flexible polyether diamine is 230 to 600, and the primary amine functionality is 2; the water content of the low-water toluene is not higher than 0.05%, and the mass fraction of ethanol is not lower than 99.5%.

[0014] In step (3), the mass fraction of maleic anhydride-grafted styrene-butadiene-styrene block copolymer in low-water toluene is 10% to 15%; after the block copolymer is dissolved, pre-oxidized adhesive powder is added at 50 to 65°C and 400 to 800 r / min and stirred for 30 to 60 min.

[0015] In step (3), the mass fraction of amino-grafted nano-silica in the low-water toluene dispersion is 5% to 10%. After adding the dispersion, stir for 10 to 20 minutes, then add flexible polyether diamine. After the ethanol is added, stir for 30 to 60 minutes, let stand for 30 to 60 minutes, filter and wash with ethanol, and then vacuum dry at 50 to 60°C.

[0016] In one specific embodiment, based on 100 parts by weight of pre-oxidized adhesive powder (dry basis), the amount of maleic anhydride-grafted styrene-butadiene-styrene block copolymer is 22.5 parts by weight; the ratio of the total molar amount of primary amine groups to the molar amount of anhydride groups is 0.70, and the primary amine groups provided by amino-grafted nano silica account for 25% of the total molar amount of primary amine groups; the first addition of ethanol has a cloud point of 0.78V, and the cumulative addition of ethanol has a cloud point of 1.80V.

[0017] In step (4), the base asphalt is No. 70 road petroleum asphalt; the base asphalt is first heated to 165-175℃, and the composite particles are added in batches at 800-1200r / min and stirred for 15-30min, then sheared at 3000-4500r / min for 30-60min, and then developed at 155-165℃ and 300-600r / min for 60-120min.

[0018] The present invention also provides a composite particle for preparing synergistically modified asphalt, which is obtained by steps (1) to (3) of the above preparation method.

[0019] The present invention also provides a synergistic modified asphalt, which is prepared by mixing the above-mentioned composite particles with the base asphalt in step (4).

[0020] Compared with the prior art, the present invention has the following beneficial effects: (1) Maleic anhydride-grafted SBS is first impregnated with pre-oxidized rubber powder. When the system is close to the cloud point and before free flocculent matter appears, amino-grafted nano-silica is introduced so that the grafted nano-silica can enter the outer layer of the rubber powder together during the precipitation of the coated polymer. The primary amine groups on the surface of nano-silica can participate in the ring-opening reaction of the anhydride group, which helps to reduce the tendency of nano-silica to migrate as independent high-density particles.

[0021] (2) Hydrogen peroxide aqueous phase oxidation introduces oxygen-containing groups into the surface of the rubber powder while retaining the internal vulcanization network. Maleic anhydride-grafted SBS forms a flexible coated phase after solution impregnation and ethanol-induced precipitation. Flexible polyether diamine and amino-grafted nano-silica jointly provide primary amine groups, enabling the coated phase to form flexible chain connection points and inorganic connection points. Compared to directly adding each component to asphalt, pre-forming composite particles helps reduce relative migration during high-temperature standing.

[0022] (3) By controlling the primary amine groups provided by amino-grafted nano silica to 15%–35% of the total primary amine groups, and controlling the molar ratio of the total primary amine groups to the anhydride groups to 0.65–0.75, an equivalent balance can be maintained between the inorganic linking points and the flexible polyether chains. This range allows nano silica to participate in the formation of coated particles, and also helps to avoid excessive inorganic linking points, which would lead to particle network reinforcement and viscosity increase at the construction temperature.

[0023] (4) After washing and drying, the composite particles can be directly metered and added to the base asphalt, and elastomeric modified asphalt can be prepared by conventional mixing, shearing and development equipment. The results of the example comparison with those of non-amino-grafted nano-silica, post-granulation addition, direct blending of the same components and pre-addition of nano-silica show that this method can simultaneously reduce the difference in softening point between the upper and lower sections, the difference in the mass fraction of hot toluene insoluble matter, and the changes in viscosity and softening point during high-temperature storage, and keep the rotational viscosity at 175℃ within the range of construction viscosity. Detailed Implementation

[0024] In this invention, low-water toluene refers to toluene with a water content of no more than 0.05%; V turbidity point refers to the volume of ethanol when the turbidity of the standard sample with the same composition lasts for 60 seconds, and is calculated based on the mass ratio of the standard sample to the master batch dispersion; it can be calculated using the primary amine content by hydrochloric acid adsorption-sodium hydroxide back titration and after blank correction by ungrafted nano-silica.

[0025] Hydrogen peroxide treatment is carried out in a reactor with jacketed heat exchange and exhaust piping; toluene and ethanol operations are conducted in closed, explosion-proof equipment with condensation recovery.

[0026] The waste tire vulcanized rubber powder used in the preparation examples, embodiments, and comparative examples was 60 mesh; the average particle size of the hydrophilic nano-silica was 20 nm, and the specific surface area was 200 m². 2 / g; 3-aminopropyltriethoxysilane purity is 98.0%; maleic anhydride grafted SBS anhydride group content is 0.18mmol / g; flexible polyether diamine number average molecular weight is 400, primary amine functionality is 2, primary amine group content is 5.00mmol / g; toluene moisture content is not higher than 0.05%, ethanol mass fraction is 99.5%; base asphalt is No. 70 road petroleum asphalt.

[0027] Preparation Example 1: Pre-oxidized Gum Powder Weigh 2500g of waste tire vulcanized rubber powder, wash it three times with deionized water, filter it, and dry it at 55℃ and vacuum degree -0.085MPa for 10h to make the moisture content no higher than 0.5%.

[0028] 10500g of a 20.0% hydrogen peroxide aqueous solution was added to a reactor equipped with a jacketed heat exchanger and an exhaust pipe. The dried adhesive powder was then added in batches over 20 minutes at 20°C and 300 rpm. After the addition was complete, the temperature was raised to 65°C within 30 minutes, the rotation speed was adjusted to 350 rpm, and the reaction was maintained at this temperature for 2 hours and 15 minutes.

[0029] The reactants were cooled to 30°C, and 2500g of a 10.0% sodium bisulfite aqueous solution was added over 30 minutes. Stirring continued for another 30 minutes; no color development was observed on the peroxide test paper. The mixture was filtered, washed three times with deionized water, and dried at 55°C under a vacuum of -0.085MPa for 12 hours. After slight depolymerization, the mixture was passed through a 40-mesh sieve to obtain pre-oxidized rubber powder.

[0030] Preparation Example 2: Amino-grafted nano-silica Weigh 100.0 g of hydrophilic nano-silica, dry it at 105 °C for 2 h, and cool it to room temperature in a desiccator. Add the dried nano-silica to a dispersion medium consisting of 1140 mL of ethanol and 60 mL of deionized water, and disperse it at 8000 r / min for 10 min to obtain a nano-silica dispersion.

[0031] Weigh 10.0 g of 3-aminopropyltriethoxysilane and add it to a mixture of 190 mL of ethanol and 10 mL of deionized water. Add 0.80 g of glacial acetic acid to adjust the pH to 5.0, and stir at 25 °C for 30 min to pre-hydrolyze the mixture. Heat the nano-silica dispersion to 60 °C and maintain the temperature at 600 rpm. Add the pre-hydrolyzed solution over 20 min, and continue the reaction for 6 h after the addition is complete.

[0032] The reactants were centrifuged at a relative centrifugal force of 6000×g for 10 min, the solid was collected, redispersed with ethanol and washed three times. The solid was dried at 55℃ and a vacuum of -0.085MPa for 10 h, slightly depolymerized, and passed through a 100-mesh sieve to obtain amino-grafted nano-silica.

[0033] Take 0.5000 g of the obtained amino-grafted nano-silica, add 50.00 mL of 0.0200 mol / L hydrochloric acid aqueous solution, sonicate for 10 min, shake for 2 h, centrifuge and collect the supernatant; back titrate with 0.0200 mol / L sodium hydroxide aqueous solution, and use the same mass of ungrafted nano-silica as a blank correction. Calculated based on the amount of hydrochloric acid consumed, the primary amino group content of the obtained amino-grafted nano-silica is 0.35 mmol / g.

[0034] The primary amino group content q of amino-grafted nano-silica is calculated as q = c × (V0 - V1) / m, where q is in mmol / g, c is the concentration of sodium hydroxide standard solution in mol / L, V0 is the sodium hydroxide back-titration volume of the same mass of ungrafted nano-silica blank solution in mL, V1 is the sodium hydroxide back-titration volume of the sample supernatant in mL, and m is the sample mass in g.

[0035] Preparation Example 3: Amine-grafted nano-silica provides composite particles with 15.0% primary amine groups. Add 39.375 g of maleic anhydride-grafted SBS and 275.625 g of low-water toluene to the reactor. Under nitrogen protection and at 60 °C, stir at 500 r / min for 60 min to dissolve the maleic anhydride-grafted SBS. Add 175.0 g of the pre-oxidized rubber powder obtained in Preparation Example 1 and stir at 600 r / min for 45 min to impregnate the pre-oxidized rubber powder with the polymer solution.

[0036] A 20.0g standardization sample was prepared using the same batch of raw materials at the same mass ratio, and ethanol was added dropwise at 60℃ and 600r / min. When the amount of ethanol added reached 12.0mL, the turbidity of the standardization sample lasted for 60s. Based on the 490.0g of the main batch of adhesive powder-polymer dispersion, the turbidity point (V_turbidity point) of the main batch of ethanol was calculated to be 294mL.

[0037] Maintain the temperature of the main batch material at 60℃ and the rotation speed at 600r / min. Add 230mL of ethanol within 15min. At this time, the amount of ethanol added is 0.78V turbidity point. The material is slightly opalescent and no free flocculent matter appears.

[0038] 2.126 g of the amino-grafted nano-silica obtained in Preparation Example 2 was added to 26.25 g of low-water toluene and pre-dispersed at 8000 r / min for 5 min. The pre-dispersed mixture and 34.93 g of low-water toluene were added sequentially over 10 min, while 45 mL of ethanol was added at a uniform rate, ensuring the material maintained a slightly opalescent state during the addition of low-water toluene. 0.843 g of flexible polyether diamine was mixed with 6.157 g of low-water toluene and added over 10 min, followed by continued stirring for another 10 min.

[0039] Add 254 mL of ethanol over 30 minutes, bringing the total ethanol addition to 529 mL, which corresponds to the 1.80V cloud point. Stir at 60°C and 600 rpm for 45 minutes, then stop stirring and allow to stand at 60°C for 45 minutes to mature. Cool the material to 30°C, filter, wash three times with ethanol, and dry at 55°C and -0.085 MPa vacuum for 12 hours to achieve slight depolymerization, yielding composite particles.

[0040] In this preparation example, the molar ratio of the total amount of primary amine groups to the anhydride groups is 0.70, and the primary amine groups provided by amino-grafted nano silica account for 15.0% of the total amount of primary amine groups.

[0041] Preparation Example 4: Amine-grafted nano-silica provides composite particles with 25.0% primary amine groups. Except for changing the amount of amino-grafted nano-silica to 3.544 g and the amount of flexible polyether diamine to 0.744 g, the amounts of other raw materials and the operation were the same as in Preparation Example 3. 3.544 g of amino-grafted nano-silica was pre-dispersed in 43.68 g of low-water toluene, and then 17.50 g of low-water toluene was added. 0.744 g of flexible polyether diamine was mixed with 6.256 g of low-water toluene and then added. The mixture was filtered, washed, dried, and slightly depolymerized to obtain composite particles.

[0042] In this preparation example, the molar ratio of the total amount of primary amine groups to the anhydride groups is 0.70, and the primary amine groups provided by amino-grafted nano silica account for 25.0% of the total amount of primary amine groups.

[0043] Preparation Example 5: Amine-grafted nano-silica provides composite particles with 35.0% primary amine groups. Except for changing the amount of amino-grafted nano-silica to 4.961 g and the amount of flexible polyether diamine to 0.645 g, the amounts of other raw materials and the operation were the same as in Preparation Example 3. 4.961 g of amino-grafted nano-silica was pre-dispersed in 61.18 g of low-water toluene; 0.645 g of flexible polyether diamine was mixed with 6.355 g of low-water toluene and then added. The mixture was filtered, washed, dried, and slightly depolymerized to obtain composite particles.

[0044] In this preparation example, the molar ratio of the total amount of primary amine groups to the anhydride groups is 0.70, and the primary amine groups provided by amino-grafted nano silica account for 35.0% of the total amount of primary amine groups.

[0045] Preparation Example 6: Coated Particles Without Amino-Grafted Silica Nanoparticles Except for omitting the addition of amino-grafted nano-silica and changing the amount of flexible polyether diamine to 0.992 g, the amounts of other raw materials and the operation were the same as in Preparation Example 4. After adding a total of 230 mL of ethanol, 61.18 g of low-water toluene was added over 10 min, while 45 mL of ethanol was added at a uniform rate; 0.992 g of flexible polyether diamine was mixed with 6.008 g of low-water toluene and then added. Another 254 mL of ethanol was added, followed by ripening, filtration, washing, drying, and slight depolymerization to obtain coated particles without amino-grafted nano-silica.

[0046] In this preparation example, the molar ratio of the total amount of primary amine groups to the anhydride groups is 0.70, and all primary amine groups are provided by flexible polyether diamine.

[0047] Example 1 Weigh 1000g of base asphalt and heat it to 170℃. Weigh the actual dry mass of the entire batch of composite particles obtained in Preparation Example 3, divide it into 5 equal parts, and add them sequentially under stirring at 1000r / min, with an interval of 2min between each addition. The entire batch of composite particles was prepared based on 175.0g of pre-oxidized rubber powder dry basis. After the addition was complete, continue stirring for 20min.

[0048] Maintain the material temperature at 170℃ and shear at 4000 r / min for 45 min; then reduce the temperature to 160℃ and stir at 450 r / min for 90 min to obtain modified asphalt.

[0049] Example 2 Except for changing the batch of composite particles obtained in Preparation Example 3 to the batch of composite particles obtained in Preparation Example 4, the other raw materials, dosages and preparation conditions were the same as in Example 1, and modified asphalt was obtained.

[0050] Example 3 Except for replacing the batch of composite particles obtained in Example 3 with the batch of composite particles obtained in Example 5, the other raw materials, dosages and preparation conditions were the same as in Example 1, and modified asphalt was obtained.

[0051] Comparative Example 1: Except for replacing the batch of composite particles obtained in Preparation Example 4 with the batch of coated particles obtained in Preparation Example 6, the other raw materials, dosages and preparation conditions were the same as in Example 2, and modified asphalt was obtained.

[0052] Comparative Example 2: The control-coated particles were prepared according to the formulation of Preparation Example 4, with the following difference: after adding a total of 230 mL of ethanol, amino-grafted nano-silica was not added; instead, 61.18 g of low-water toluene was added within 10 min, along with 45 mL of ethanol; the flexible polyether diamine remained at 0.744 g, diluted with 6.256 g of low-water toluene before being added; and then another 254 mL of ethanol was added. The remaining preparation conditions were the same as in Preparation Example 4, resulting in the control-coated particles.

[0053] 1000g of base asphalt was weighed and heated to 170℃. Under stirring at 1000 rpm, the obtained batch of coated particles was added in 5 portions, followed by the control particles. Stirring was continued for 20 min, then 3.544g of the amino-grafted nano-silica obtained in Preparation Example 2 was added, and stirring was continued for 10 min. Subsequently, the asphalt was treated according to the shearing and growth conditions of Example 2 to obtain modified asphalt. This comparative example used the same amounts of pre-oxidized rubber powder, maleic anhydride-grafted SBS, amino-grafted nano-silica, and flexible polyether diamine as in Example 2.

[0054] Comparative Example 3: Weigh 1000g of base asphalt, heat to 170℃, add 39.375g of maleic anhydride-grafted SBS, and stir at 1000r / min for 30min. Add 175.0g of the pre-oxidized rubber powder obtained in Preparation Example 1 in 5 portions, stirring for 20min after each addition; then add 3.544g of the amino-grafted nano-silica obtained in Preparation Example 2 and 0.744g of flexible polyether diamine, and continue stirring for 10min. Subsequently, shear at 4000r / min at 170℃ for 45min, and then stir and develop at 450r / min at 160℃ for 90min to obtain modified asphalt with direct blending of each component. Based on the feed amount for composite particle preparation, this comparative ratio is the same as the feed amount of each functional component in Example 2.

[0055] Comparative Example 4: The composite particles with pre-added amino-grafted nano-silica were prepared according to the formulation of Preparation Example 4, with the difference being: after the pre-oxidized adhesive powder was impregnated with maleic anhydride-grafted SBS solution for 45 min, a pre-dispersion consisting of 3.544 g of amino-grafted nano-silica and 43.68 g of low-water toluene was added before the addition of ethanol, followed by the addition of 17.50 g of low-water toluene, and stirring for 15 min; then, 275 mL of ethanol was added within 15 min, along with a diluent consisting of 0.744 g of flexible polyether diamine and 6.256 g of low-water toluene, and finally, 254 mL of ethanol was added within 30 min. The remaining conditions were the same as in Preparation Example 4, resulting in composite particles with pre-added amino-grafted nano-silica.

[0056] Except for replacing the batch of composite particles obtained in Preparation Example 4 with the above-mentioned batch of composite particles with pre-added amino-grafted nano silica, the other raw materials, dosages and preparation conditions were the same as in Example 2, and modified asphalt was obtained.

[0057] Comparative Example 5: Composite particles were prepared according to the method of Preparation Example 4, except that: the amount of amino-grafted nano-silica was changed to 5.670 g, and it was pre-dispersed with 61.18 g of low-water toluene; the amount of flexible polyether diamine was changed to 0.595 g, and it was added after being diluted with 6.405 g of low-water toluene. The remaining raw materials, amounts, and preparation conditions were the same as in Preparation Example 4, and composite particles were obtained. The molar ratio of the total amount of primary amine groups to acid anhydride groups in the composite particles was 0.70, and the primary amine groups provided by the amino-grafted nano-silica accounted for 40.0% of the total amount of primary amine groups.

[0058] Except for replacing the batch of composite particles obtained in Preparation Example 4 with the above-mentioned batch of composite particles, the other raw materials, dosages and preparation conditions are the same as in Example 2, and modified asphalt is obtained.

[0059] Performance testing: Each sample was prepared in three batches independently. During the 48-hour high-temperature storage stratification test, two parallel separation tubes were used for each batch of samples; rotational viscosity was read three times consecutively on the same sample under the following test conditions. The results in the table are the arithmetic mean of the test results for each of the three batches of samples.

[0060] Stratification performance under 48-hour high-temperature storage: The test was conducted according to T0661-2025 "Segregation Test of Polymer-Modified Asphalt" in JTG 3410-2025 "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering", using storage conditions of 163℃±5℃ and 48h±1h. After freezing the segregation tube and dividing it into three equal sections (upper, middle, and lower), samples from the upper and lower sections were taken, and the softening point was determined according to T0606-2011. The difference between the softening points of the upper and lower sections was taken as the absolute value.

[0061] Separately weigh 2.000 g of the upper and lower section samples, add 200 mL of toluene, stir at 60 °C for 60 min, centrifuge at a relative centrifugal force of 12000 × g for 20 min, and collect the insoluble matter. Wash the insoluble matter three times with toluene and dry at 105 °C to constant weight. The percentage of insoluble matter to the mass of the asphalt sample is recorded as the hot toluene insoluble matter mass fraction, and the difference between the hot toluene insoluble matter mass fractions of the upper and lower sections is taken as the absolute value.

[0062] The results from two parallel separation tubes in each batch were first taken as the arithmetic mean, which was then used as the overall average of the results from the three batches. The mass fraction of insoluble matter in hot toluene, w, was calculated as w = m1 / m0 × 100%, where m0 is the mass of the upper or lower asphalt sample, and m1 is the mass of the insoluble matter in the corresponding sample after hot toluene treatment, washing, and drying to constant weight. The mass fraction difference between the upper and lower sections, Δw, was calculated as Δw = |w 下 -w 上 Calculation.

[0063] Table 1. Stratification results of softening point at 48h high-temperature storage for each embodiment and comparative example.

[0064] Table 2. Stratification results of hot toluene insolubles after 48 hours of high-temperature storage for each example and comparative example.

[0065] Changes in rotational viscosity and softening point during high-temperature storage: Each batch of samples was placed into four 250mL capped metal containers, each containing 220g of sample, and sealed. Except for the 0h sample, the remaining samples were stored in a 163℃ oven for 24h, 48h, and 72h, respectively. Independent metal containers were used at each time point, and samples were not taken repeatedly from the same container. After the specified storage time was reached, the corresponding metal containers were removed and stirred at 165℃ at 300r / min for 2min to ensure homogenization of the sample.

[0066] The construction viscosity of rubber asphalt was determined at 175℃ according to T0625-2011 "Asphalt Rotation Viscosity Test" in JTG 3410-2025; each sample was kept at a constant temperature for 15 min and then read three times, with an interval of 60 s between adjacent readings. The overall softening point after homogenization was determined according to T0606-2011. The results are shown in Tables 3 and 4.

[0067] Table 3. Rotational viscosity at 175°C for each embodiment and comparative example during high-temperature storage.

[0068] Table 4. Overall softening point of each embodiment and comparative example after homogenization during high-temperature storage.

[0069] Results analysis: In Example 2 and Comparative Example 1, the total primary amine group to anhydride group molar ratio was 0.70. Example 2 used amino-grafted nano-silica to provide 25.0% of the primary amine groups, while Comparative Example 1 used flexible polyether diamine to provide all the primary amine groups. The softening point difference between the upper and lower sections of Example 2 and Comparative Example 1 after 48 hours was 1.3℃ and 5.9℃, respectively; the difference in the mass fraction of hot toluene insolubles between the upper and lower sections was 0.7% and 3.2%, respectively; and the rotational viscosity at 175℃ increased by 0.04 Pa·s and 0.25 Pa·s, respectively, within 72 hours. These results indicate that, under the condition of constant total primary amine equivalent, allowing amino-grafted nano-silica to bear part of the primary amine equivalent and participate in the composite particle formation process is beneficial in reducing the difference in viscosity between the upper and lower sections and during high-temperature settling.

[0070] Example 2 used the same amounts of pre-oxidized rubber powder, maleic anhydride-grafted SBS, amino-grafted nano-silica, and flexible polyether diamine as Comparative Example 2. The difference lies in that in Example 2, amino-grafted nano-silica was introduced when the ethanol addition reached a cloud point of 0.78V and the coated polymer was close to precipitation, while in Comparative Example 2, amino-grafted nano-silica was added to the asphalt after the coated particles were formed. Compared to Comparative Example 2, the softening point difference between the upper and lower sections in Example 2 decreased from 4.3℃ to 1.3℃, the difference in the mass fraction of hot toluene insolubles decreased from 2.5% to 0.7%, and the rotational viscosity at 175℃ after 72 hours decreased from 1.33 Pa·s to 1.19 Pa·s. This demonstrates that, with the same final raw material composition, adding amino-grafted nano-silica during the composite particle formation stage is more beneficial in reducing relative migration than adding it separately after formation.

[0071] Based on the feed amount for composite particle preparation, the feed amounts of each functional component were the same in Example 2 and Comparative Example 3. In Example 2, composite particles were formed first, and then added to the base asphalt; in Comparative Example 3, each component was directly added to the base asphalt. The difference in softening points between the upper and lower sections was 1.3℃ and 6.9℃, respectively; the difference in the mass fraction of hot toluene insolubles was 0.7% and 4.4%, respectively; the rotational viscosity at 175℃ increased by 0.04 Pa·s and 0.36 Pa·s, respectively, within 72 hours; and the overall softening point increased by 0.4℃ and 3.2℃, respectively, after homogenization. This comparison demonstrates that the material formation history established by first forming recyclable composite particles cannot be replaced by direct blending of the same components in asphalt.

[0072] Example 2 and Comparative Example 4 had the same raw material composition, functional group equivalent, and final asphalt preparation conditions. In Example 2, amino-grafted nano-silica was introduced after the cumulative addition of 0.78V cloud point ethanol, and ethanol was added simultaneously with the addition of its toluene dispersion to maintain a slightly opalescent state; in Comparative Example 4, the amino-grafted nano-silica was mixed into a homogeneous polymer solution before the addition of ethanol. Compared to Comparative Example 4, the softening point difference between the upper and lower sections in Example 2 decreased from 2.9℃ to 1.3℃, the difference in the mass fraction of hot toluene insolubles decreased from 1.8% to 0.7%, and the increase in rotational viscosity at 175℃ over 72 hours decreased from 0.13 Pa·s to 0.04 Pa·s. These results indicate that the timing of the addition of amino-grafted nano-silica affects the storage performance of the resulting composite particles.

[0073] In Example 3 and Comparative Example 5, the total primary amine group to anhydride group molar ratio was 0.70, and the proportion of primary amine groups provided by amino-grafted nano-silica was 35.0% and 40.0%, respectively. After this proportion increased from 35.0% to 40.0%, the difference in softening points between the upper and lower sections increased from 1.6℃ to 1.9℃, the difference in the mass fraction of hot toluene insolubles increased from 0.9% to 1.3%, and the rotational viscosity at 175℃ at 0h and 72h increased from 1.31 Pa·s and 1.42 Pa·s to 1.47 Pa·s and 1.64 Pa·s, respectively. This indicates that further increasing the primary amine equivalent provided by amino-grafted nano-silica did not further reduce the stratification difference and increased the viscosity at the application temperature.

[0074] In Examples 1, 2, and 3, the proportions of primary amine groups provided by amino-grafted nano-silica were 15.0%, 25.0%, and 35.0%, respectively. Example 1 exhibited a lower rotational viscosity at 175°C; Example 2 showed smaller differences in softening point between the upper and lower portions, smaller differences in the mass fraction of hot toluene-insoluble matter, and smaller changes over time; Example 3 had a higher overall softening point, but its viscosity at the application temperature also increased accordingly. Therefore, when the total amount of primary amine groups remains constant, the primary amine equivalent distribution between amino-grafted nano-silica and flexible polyether diamine simultaneously affects both storage stability and application viscosity.

[0075] This method introduces amino-grafted nano-silica when maleic anhydride-grafted SBS is nearing precipitation, inducing it to enter the composite particle formation stage. Compared with comparative examples that do not contain this grafted silica, are added after granulation, are directly blended with the same components, and are added in advance, the modified asphalt exhibits reduced differences in softening point between the upper and lower sections, differences in the mass fraction of hot toluene-insoluble matter, and viscosity changes during high-temperature storage.

Claims

1. A method for preparing synergistically modified asphalt, characterized in that, Includes the following steps: (1) Waste tire vulcanized rubber powder was oxidized in aqueous phase with hydrogen peroxide solution. After oxidation, the residual peroxide was consumed with sodium bisulfite. The powder was filtered, washed and dried to obtain pre-oxidized rubber powder. (2) The hydrophilic nano silica was dispersed in an ethanol-water medium. 3-aminopropyltriethoxysilane was pre-hydrolyzed in an acidic ethanol-water medium and then added to the nano silica dispersion to condense the 3-aminopropyltriethoxysilane with the surface of the nano silica. The nano silica was then separated, washed and dried to obtain amino-grafted nano silica. (3) Dissolve maleic anhydride-grafted styrene-butadiene-styrene block copolymer in low-water toluene, add the pre-oxidized adhesive powder and stir to wet, first add ethanol with a cloud point of 0.70-0.85V to make the system slightly opalescent and free flocculent matter visible to the naked eye, then add the amino-grafted nano silica low-water toluene dispersion, and simultaneously add ethanol to maintain the above state during the addition process; after the addition is completed, add flexible polyether diamine with a primary amine functionality of 2, and continue to add ethanol to make the cumulative amount of ethanol added reach a cloud point of 1.5-2.5V. After stirring, standing and aging, filtration, washing with ethanol and drying, composite particles are obtained. Of which, based on 100 parts by weight of pre-oxidized adhesive powder (dry basis), the maleic anhydride-grafted styrene-butadiene-styrene block copolymer is 20-25 parts by weight; the ratio of the total molar amount of primary amine groups of amino-grafted nano-silica to the total molar amount of primary amine groups of flexible polyether diamine and the molar amount of anhydride groups of the block copolymer is 0.65-0.75, and the primary amine groups provided by the amino-grafted nano-silica account for 15%-35% of the total molar amount of primary amine groups; (4) The composite particles are added to the base asphalt and stirred, sheared and developed to obtain synergistically modified asphalt; wherein, based on 100 parts by mass of base asphalt, the amount of the composite particles added is 15 to 20 parts by mass based on the dry basis of the pre-oxidized rubber powder added when preparing the composite particles.

2. The preparation method according to claim 1, characterized in that, In step (1), the waste tire vulcanized rubber powder is 40-80 mesh and the initial moisture content is not higher than 0.5%; the mass ratio of the waste tire vulcanized rubber powder to the hydrogen peroxide aqueous solution is 1:4 to 1:5, and the mass fraction of the hydrogen peroxide aqueous solution is 20% to 25%; the oxidation temperature is 60-70℃, and the oxidation time is 2-2.5h; after the oxidation is completed, the temperature is lowered to below 35℃, and a sodium bisulfite aqueous solution with a mass fraction of 5% to 10% is added until the residual peroxide test is negative.

3. The preparation method according to claim 1, characterized in that, In step (2), the nominal primary particle size of the hydrophilic nano-silica is 10–30 nm, and the specific surface area is 150–250 m². 2 / g; based on 100 parts by mass of nano-silica, 3-aminopropyltriethoxysilane is 8-12 parts by mass; the mass ratio of ethanol to water in the pre-hydrolysis medium is 90:10-95:5, the pH is 4.5-5.5, the pre-hydrolysis temperature is 20-30℃, and the pre-hydrolysis time is 20-40 min; the condensation reaction temperature is 50-65℃, and the reaction time is 4-8 h; the available primary amine content of the obtained amino-grafted nano-silica is 0.25-0.45 mmol / g.

4. The preparation method according to claim 1, characterized in that, In step (3), the anhydride content of the maleic anhydride-grafted styrene-butadiene-styrene block copolymer is 0.12 to 0.22 mmol / g; the number average molecular weight of the flexible polyether diamine is 230 to 600, and the primary amine functionality is 2; the water content of the low-water toluene is not higher than 0.05%, and the mass fraction of the ethanol is not lower than 99.5%.

5. The preparation method according to claim 1, characterized in that, In step (3), the mass fraction of the maleic anhydride-grafted styrene-butadiene-styrene block copolymer in low-water toluene is 10% to 15%; after the block copolymer is dissolved, pre-oxidized adhesive powder is added at 50 to 65°C and 400 to 800 r / min and stirred for 30 to 60 min.

6. The preparation method according to claim 1 or 5, characterized in that, In step (3), the mass fraction of amino-grafted nano-silica in the low-water toluene dispersion is 5% to 10%; after adding the dispersion, stir for 10 to 20 minutes, then add flexible polyether diamine; after the ethanol is added in total, stir for 30 to 60 minutes, let stand for 30 to 60 minutes, filter and wash with ethanol, and then vacuum dry at 50 to 60°C.

7. The preparation method according to any one of claims 1 to 5, characterized in that, In step (3), based on 100 parts by mass of pre-oxidized adhesive powder (dry basis), the maleic anhydride-grafted styrene-butadiene-styrene block copolymer is 22.5 parts by mass; the ratio of the total molar amount of primary amine groups to the molar amount of anhydride groups is 0.70, and the primary amine groups provided by amino-grafted nano silica account for 25% of the total molar amount of primary amine groups; the first addition of ethanol has a cloud point of 0.78V, and the cumulative addition of ethanol has a cloud point of 1.80V.

8. The preparation method according to any one of claims 1 to 5, characterized in that, In step (4), the base asphalt is No. 70 road petroleum asphalt; the base asphalt is first heated to 165-175℃, and the composite particles are added in batches at 800-1200r / min and stirred for 15-30min, then sheared at 3000-4500r / min for 30-60min, and then developed at 155-165℃ and 300-600r / min for 60-120min.

9. A composite particle for preparing synergistically modified asphalt, characterized in that, It is prepared by steps (1) to (3) of the preparation method according to any one of claims 1 to 7.

10. A synergistically modified asphalt, characterized in that, The composite particles described in claim 9 are prepared by mixing them with the base asphalt in step (4) of claim 1.

Citation Information

Patent Citations

  • Chemical modified rubber asphalt with stable performance and preparation method thereof

    CN103205131A

  • A rubber powder modified asphalt material with high storage stability and its preparation method

    CN107936590B

  • Modified asphalt composite particles based on waste rubber powder, and preparation method thereof

    CN110256745A

  • A rubber powder modified asphalt and its preparation method

    CN115678299B